Dynamic, Over-Valgus Correction Without Osteotomy for Nonunion of Subtrochanteric Hip Fractures Using a Dynamic Hip Screw - Alberto D. Delgado-Martínez; Hermenegildo Cañada-Oya; Cristina Zarzuela-Jiménez (Applied Sciences)
Subtrochanteric nonunion is especially challenging. Extramedullary fixation using fixed-angle devices with a closing lateral wedge osteotomy is the standard surgical procedure for restoring the hip’s normal alignment and achieving bone union. However, this procedure is technically demanding and relies on devices that facilitate bone union in a non-dynamic manner, along with the limitations that this type of fixation entails, especially in this highly biomechanically stressed area. This paper aims to describe a novel surgical technique to heal subtrochanteric nonunion based on dynamic fixation performed through an over-valgus correction of the hip and fixed with a dynamic hip screw (DHS). Between March 2022 and July 2023, five patients diagnosed with nonunion of a subtrochanteric fracture were operated on by a single surgeon and followed prospectively. The average age of the patients was 64 (range: 34–85). The mean duration of surgery was 112 min (range: 63–153). The femoral neck angle before surgery was 120° (range: 110°–122°) and 147° (range: 142°–150°) after surgery. The mean leg length increased by 8 mm (range: 6–12). The Harris hip score improved from 38 points (range: 30–44) to 90 points (range: 88–96), corresponding to excellent or good results. All patients healed without major complications and were asymptomatic after 12 months of follow-up. In conclusion, over-valgus correction using a DHS is a novel technique that seems helpful for subtrochanteric nonunion. It allows for dynamic fixation, offering the advantages of dynamic fixation, especially in this high-stress area. It is also performed without osteotomy, making it a less demanding technique than the current methods described.